Relationships among health-related behaviors, smartphone dependence, and sleep duration in female junior college students - Shang-Yu Yang; Kai-Li Chen; Pin-Hsuan Lin; Po-Yu Wang (Wolters Kluwer Medknow Publications, 2019)
Introduction: Inadequate sleep is common among adolescents. Females have been found to have higher sleep requirement than that in males. This study aimed at (1) investigating the associations of sleep duration with smartphone dependence and a health-promoting lifestyle, and (2) identifying predictor(s) of inadequate sleep among adolescent females. Methods: This questionnaire-based cross-sectional study recruited 385 female junior college students (mean age: 17.50 ± 3.30 years) at a single tertiary education institute in December 2014. The questionnaire comprised three parts: (1) demographic/anthropometric characteristics (i.e., age, body mass index) and habits of alcohol/tobacco consumption, (2) smartphone dependence score according to the participant's response to four questions rated with five-point Likert scale, and (3) scores on compliance with six dimensions of the health-promoting lifestyle profile (HPLP), including nutrition, health responsibility, self-actualization, interpersonal support, exercise, stress management, and total score. Correlations of the study parameters and sleep adequacy (defined as ≥7 h) were investigated. Results: The mean sleep duration of the participants was 7.35 ± 1.49 h. Logistic regression analysis demonstrated significant negative correlation between smartphone dependence and sleep duration (P < 0.01), as well as positive associations of sleep duration with the nutrition (P < 0.01), health responsibility (P < 0.05), stress management (P < 0.01) dimensions, and total score (P = 0.01) of HPLP. Stepwise regression further showed that smartphone dependence was the only significant predictor of inadequate sleep (B: −0.06; standard error: 0.02; P < 0.01). Conclusion: The results of the present study underscore the importance of promoting a healthy lifestyle including prevention of smartphone dependence in maintaining healthy sleep habits in adolescent females.